Nujiangexathone A, a novel compound from Garcinia nujiangensis, suppresses cervical cancer growth by targeting hnRNPK. Issue 2 (1st October 2016) - Zhang, Li; Feng, Jiling; Kong, Siyuan; Wu, Man; Xi, Zhichao; Zhang, Baojun; Fu, Wenwei; Lao, Yuanzhi; Tan, Hongsheng; Xu, Hongxi
Highlights: Recently, the protein hnRNPK has emerged as an important player in carcinogenesis process. The therapeutic strategies targeted on the protein hnRNPK are very limited. The effect of small molecules on hnRNPK protein hasn't been reported in cervical cancer. Our study indicated that NJXA showed antitumor effect in vitro and in vivo by targeting hnRNPK protein. NJXA is especially applicable as a potential candidate for treating cervical cancer with abnormally high hnRNPK expression. Abstract: Cervical cancer is among the most frequently diagnosed cancers in females worldwide. Nujiangexathone A (NJXA), a novel compound from Garcinia nujiangensis, has been shown to have anti-cancer potential. In this study, the anti-tumor effects and the underlying mechanisms of NJXA action were investigated. Our results suggested that NJXA induced G0/G1 cell cycle arrest in HeLa and SiHa cells by down-regulating cyclins B1, E1, and A and cyclin-dependent kinases 2, 4 and 6, while selectively restoring p27. Using two-dimensional gel electrophoresis, we showed that NJXA reduced the expression of heterogeneous nuclear ribonucleoprotein K (hnRNPK) by accelerating ubiquitin-proteasome-dependent hnRNPK degradation, which then induced cell cycle arrest through the c-Myc-cyclin/Cdk-Rb-E2F1 pathway. The loss-of-function study showed NJXA induced cell cycle arrest was mediated by down regulation of hnRNPK protein. In vivo results further confirmed the tumor inhibitory effect of NJXA via the down-regulation of hnRNPK, and NJXA induced no apparent toxicity. Our study suggests that NJXA may be a novel anti-cancer drug candidate, especially for treating cancers with abnormally high hnRNPK expression.